Interventions for Indigenous Peoples making health decisions: a systematic review - Janet Jull; Kimberly Fairman; Sandy Oliver; Brittany Hesmer; Abdul Kareem Pullattayil; Not Deciding Alone Team (BMC, 2023)
Abstract Background Shared decision-making facilitates collaboration between patients and health care providers for informed health decisions. Our review identified interventions to support Indigenous Peoples making health decisions. The objectives were to synthesize evidence and identify factors that impact the use of shared decision making interventions. Methods An Inuit and non-Inuit team of service providers and academic researchers used an integrated knowledge translation approach with framework synthesis to coproduce a systematic review. We developed a conceptual framework to organize and describe the shared decision making processes and guide identification of studies that describe interventions to support Indigenous Peoples making health decisions. We conducted a comprehensive search of electronic databases from September 2012 to March 2022, with a grey literature search. Two independent team members screened and quality appraised included studies for strengths and relevance of studies' contributions to shared decision making and Indigenous self-determination. Findings were analyzed descriptively in relation to the conceptual framework and reported using guidelines to ensure transparency and completeness in reporting and for equity-oriented systematic reviews. Results Of 5068 citations screened, nine studies reported in ten publications were eligible for inclusion. We categorized the studies into clusters identified as: those inclusive of Indigenous knowledges and governance ("Indigenous-oriented")(n = 6); and those based on Western academic knowledge and governance ("Western-oriented")(n = 3). The studies were found to be of variable quality for contributions to shared decision making and self-determination, with Indigenous-oriented studies of higher quality overall than Western-oriented studies. Four themes are reflected in an updated conceptual framework: 1) where shared decision making takes place impacts decision making opportunities, 2) little is known about the characteristics of health care providers who engage in shared decision making processes, 3) community is a partner in shared decision making, 4) the shared decision making process involves trust-building. Conclusions There are few studies that report on and evaluate shared decision making interventions with Indigenous Peoples. Overall, Indigenous-oriented studies sought to make health care systems more amenable to shared decision making for Indigenous Peoples, while Western-oriented studies distanced shared decision making from the health care settings. Further studies that are solutions-focused and support Indigenous self-determination are needed.